Pengaruh Serbuk Besi Dari Limbah Bubut Sebagai Subtitusi Agregat Halus Dan Variasi Tawas Sebagai Subtitusi Agregat Kasar Terhadap Kuat Tekan Beton - Febryansah, Febryansah; Setiawan, Arman; Hijriah, Hijriah (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
This study aims to analyze the relationship of compressive strength of concrete with iron powder mixture from lathe waste by 10% and alum variation by 0%, 5%, 10%, 15%, 20% and 25%. The method of this study is to compare the compressive strength of normal concrete with the compressive strength of concrete variations of iron powder and alum. The percentage of iron powder of 10% and the percentage of alum of 0% experienced a decrease in the compressive strength value against normal concrete by 8.7%, which used an iron lathe of 10% and alum of 5% experienced a drastic decrease against the compressive strength of normal concrete by 30.4%. It can be concluded that 10% iron lathe impersonation as a substitution of fine aggregates and variations of alum of 0%, 5%, 10%, 15%, 20% and 25% as substitutions of coarse aggregates lead to a decrease in the compressive strength value of concrete